Estudio de factibilidad para la creación de un aplicativo móvil para reservas en las peluquerías y centros de estética o belleza en Cali (2020)
The technological advances of recent times have simplified people's lives and made it much easier for them to access services and products that previously required more complex management. Mobile applications emerge as one of the many technological alternatives that really meet the description of "at hand", as they can be installed and used on any mobile device, anytime, anywhere. This research work focused on showing the feasibility of creating a mobile application for scheduling appointments in beauty and health services for the city of Cali, which also becomes a project of entrepreneurship and technological advancement for the city and the Department. Therefore, the problem statement, the contextualization of the problem, the establishment of the objectives and the literary review to select the arguments and theoretical bases that supported the development of the project were carried out. In addition, a qualitative approach research was used, a descriptive type in which they applied an interview to beauty and health professionals, and a survey of the public consuming these services to obtain market information; The technical and legal study was developed to validate the operational and administrative feasibility and, finally, a financial study was used to analyze the profitability of the project.